2001
DOI: 10.1515/zna-2001-0501
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Molten Alkali Nitrates

Abstract: Molecular dynamics (MD) simulations have been performed for several pure alkali nitrate melts. Special attention was paid to the examination o f the interaction potential: macroscopic quantities like pressure were calculated and compared with real values. To improve the results the commonly used potential for alkali nitrates (Coulomb pair potential and Born-type repulsion) has been extended by a short-range-attraction term to meet the real behaviour o f the liquid.With these improved potentials, simulations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…In this study, cation diffusion coefficients decrease with increased size and mass. A similar trend in cation self-diffusion has been shown in a prior molecular dynamics study, 42 where it was demonstrated that the diffusion coefficient was insensitive to the cations mass and sensitive to the ionic radius. Nevertheless, the cause of the discrepancy between the simulated Na + cations observed here and the experimental observation remains unexplained.…”
Section: ∑ ∑supporting
confidence: 82%
“…In this study, cation diffusion coefficients decrease with increased size and mass. A similar trend in cation self-diffusion has been shown in a prior molecular dynamics study, 42 where it was demonstrated that the diffusion coefficient was insensitive to the cations mass and sensitive to the ionic radius. Nevertheless, the cause of the discrepancy between the simulated Na + cations observed here and the experimental observation remains unexplained.…”
Section: ∑ ∑supporting
confidence: 82%
“…They introduced a flexible model for the nitrate anion. Vohringer and Richter modified the intermolecular parameters for the alkali nitrate salts and were able to get better results for self-diffusivities using this modified model. Ribeiro studied the composition dependence of ionic mobilities in mixtures of two cations with a common anion .…”
Section: Introductionmentioning
confidence: 99%
“…Adya et al for the first time investigated the microscopic atomic configuration and diffusion in molten NaNO 3 by means of X-ray diffraction measurement and molecular dynamics (MD) simulation, and compared its partial structure factors and partial pair distribution functions with those of molten NaNO 2 and the eutectic mixture of the NaNO 3 -NaNO 2 system showed good additivity for the intermolecular structure because the ionic radius of NO 3 and NO 2 ions are similar owing to the presence of a lone pair on the nitrite ion [6]. After Adya et al [6], several researchers have reported the MD simulation results of molten alkali nitrates [7][8][9][10][11][12]. For example, Kato et al have reported cation dependence of the detailed structural features and ionic dynamics in molten alkali nitrates [11].…”
mentioning
confidence: 99%